SIMULATION OF FLUID FLOW THROUGH A STAINLESS STEEL GLOBE VALVE USING ENGINEERING FLUID DYNAMICS - Nguyen Huu Tho (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2021)
Globe valves are often used in many practical application of industry with the aim of controlling the fluid flow through the valve. Valve design ensuring an operation capacity plays an important role for engineers. This paper presents the design and simulation of fluid flow through the globe valve using CAD/CAE tools such as Autodesk CFD. Besides, design of experiment technique Box-Behnken is used to integrate the CFD simulation to identify the optimal design parameters of the globe valve. These parameters are inlet pressure, orifice diameter, and outlet clearance. The results showed that the optimal parameters are appropriate to improve the valve design to ensure the maximum fluid flow rate.